Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning Untuk Siswa SMP Kelas VII Pada Mata Pelajaran IPA - Zuliarni; ririn rahma weni; Meldi Ade Kurnia Yusri; Eldarni (Journal of Pedagogy and Online Learning, 2023)
This study aims to produce Student Worksheets (LKPD) Based on Problem Based Learning in Science Subjects on environmental pollution at SMPN 2 Bayang Utara and to find out students' responses to the developed LKPD. The research method used is research and development (Reseach and Development) with the ADDIE development model developed by Dick and Carry. This research has 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The product validation test was carried out by 3 validators consisting of 2 media expert validators and 1 material expert validator. Product trials were carried out on 14 students of SMPN 2 Bayang Utara with the aim of knowing the practicality of the product being developed. The results showed that the product produced was "Very Valid" to be used in the learning process on science material for class VII SMP. The results of the media expert validator's assessment of problem-based learning-based worksheets obtained descriptive assessment results in the "Very Valid" category getting an average of 4.78 with a percentage of 95%. The results of the assessment of the material validator in the "Very Valid" category get an average of 4.82 with a percentage of 96%. Based on the practicality test results, it gets an average of 4.70 with a percentage of 94%, including the "Very Practical" category. Based on the results of the validation and practicality tests, it can be concluded that the problem-based learning worksheet product is suitable for use in the learning process.